Comparison of the systemic inflammatory response index and the systemic immune-inflammatory index in pediatric community–acquired pneumonia caused by respiratory syncytial virus and Mycoplasma pneumoniae - Zhou, Hui-Hui; Qian, Kai-Li (Frontiers in Pediatrics, 2025)
ObjectiveThis study aims to compare the systemic inflammatory response index (SIRI) and the systemic immune-inflammatory index (SII) in pediatric community–acquired pneumonia (CAP) caused by the respiratory syncytial virus (RSV) and Mycoplasma pneumoniae (Mp).MethodsThe study included 120 children with single RSV infection (RSV group) and 120 children with single Mp infection (Mp group). The SIRI and SII were calculated by using the formulation neutrophil × monocyte/lymphocyte and platelet × neutrophil/lymphocyte, respectively.ResultsSignificant differences were found between RSV and Mp infections in three age-stratified subgroups of <6 months, 3–5 years, and ≥5 years (p < 0.05). The proportions of children presenting with nasal stuffiness and rhinorrhea, shortness of breath, grunting, and gastrointestinal symptoms were markedly higher in the RSV group than those in the Mp group (p < 0.05). The RSV group had lower values of the SIRI and SII than the Mp group (p = 0.010; p = 0.021). The RSV group demonstrated significantly higher values in terms of duration of symptoms before admission, length of hospital stay, proportion of children requiring oxygen supplementation, and proportion of children with severe pneumonia compared with the Mp group (p < 0.05). The incidence of bronchial pneumonia and emphysema was significantly higher in the RSV group than that in the Mp group (p = 0.005; p = 0.001). However, the incidence of patchy shadow was significantly higher in the Mp group than that in the RSV group (p = 0.027).ConclusionThe SIRI and SII may offer additional value in differentiating CAP associated with RSV and Mp infections in children; both indices may serve as easily accessible blood indicators for clinical decision-making in the management of pediatric CAP.